2015
DOI: 10.1016/j.jse.2014.11.039
|View full text |Cite
|
Sign up to set email alerts
|

Identification of shoulder osteoarthritis biomarkers: comparison between shoulders with and without osteoarthritis

Abstract: Background The biological factors associated with shoulder osteoarthritis (OA) have not been elucidated. The purpose of this study was to investigate putative osteoarthritic biomarkers of the shoulder. To our knowledge, this is the first study to analyze shoulder cartilage for OA-associated genes and examine human shoulder cartilage for a novel biomarker, connexin 43 (Cx43). Materials and methods Cartilage from 16 osteoarthritic and 10 non-osteoarthritic humeral heads was assessed for expression of the follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 53 publications
3
22
0
Order By: Relevance
“…Particular MMP have been identified in higher concentrations in synovial fluid of osteoarthritic joints compared with normal joints and remain elevated for long periods of time in injured joints, thus having the potential to be reliable indicators of joint environment changes after treatment . In addition, the consistency in elevation has led authors to propose the application of MMP as markers throughout the progression of OA . The increased TIMP concentrations observed in our study are in line with a previous report in which increased TIMP‐3 expression in arthritic joints was attributed to pathological remodeling .…”
Section: Discussionsupporting
confidence: 89%
“…Particular MMP have been identified in higher concentrations in synovial fluid of osteoarthritic joints compared with normal joints and remain elevated for long periods of time in injured joints, thus having the potential to be reliable indicators of joint environment changes after treatment . In addition, the consistency in elevation has led authors to propose the application of MMP as markers throughout the progression of OA . The increased TIMP concentrations observed in our study are in line with a previous report in which increased TIMP‐3 expression in arthritic joints was attributed to pathological remodeling .…”
Section: Discussionsupporting
confidence: 89%
“…It would be crucial to correlate ultrastructural alterations inside the glenoid articular osteo‐chondral complex, showed for the first time in this article, with the different gene expression observed by many authors in shoulder (Marino et al, ; Mayan et al, ; Casagrande et al, ). In particular, Casagrande et al () showed that certain genes are markedly up‐regulated in osteoarthritic shoulders compared with non‐osteoarthritic ones; in particular, Cx43, Cox‐2, versican, collagen type I, ADAMTS5, MMP‐3, and TNF‐α expression resulted significantly increased. The same authors also suggest that these genes might be useful biomarkers for examining shoulder OA.…”
Section: Discussionmentioning
confidence: 66%
“…Increased presence of gap junction plaques and Cx43 expression have been found in synovial lining cells obtained from the knee of patients with osteoarthritis [157]. Similarly, Cx43 production is increased in the cartilage of the knee and femoral head [20] and in the shoulders of patients with osteoarthritis, suggesting that the molecule might have a role in the pathogenesis of this disease [158]. Consistent with this, Cx43 levels in osteoarthritic cartilage correlate with the expression of several pro-inflammatory and catabolic factors [158].…”
Section: Connexins In Cartilage Ligaments and Tendonsmentioning
confidence: 99%
“…Similarly, Cx43 production is increased in the cartilage of the knee and femoral head [20] and in the shoulders of patients with osteoarthritis, suggesting that the molecule might have a role in the pathogenesis of this disease [158]. Consistent with this, Cx43 levels in osteoarthritic cartilage correlate with the expression of several pro-inflammatory and catabolic factors [158]. In line with this notion, silencing of Cx43 expression protected against inflammation and joint destruction in a model of rheumatoid arthritis in rats [159].…”
Section: Connexins In Cartilage Ligaments and Tendonsmentioning
confidence: 99%